Space 4.0 – a common, democratic European space, part 5 - Ryszard S. Romaniuk; Piotr Orleański (International Journal of Electronics and Telecommunications)
Space 4.0 is a complex infrastructural, but also sociological process and political ideology, which we tried to present in the local context from various sides. Space 4.0 turned out too complex to show all its dynamically changing attributes. Space 4.0 is realized in complex economic and political environment even in the EU. Some of these issues are related to the existence of technological and economic boundaries in our region and particular political interests. Space 4.0 major goal is to build a democratic European space in real existing economic conditions, not theoretically, and in in the nearest future. Our intention was to present the image of the European space sector in an optimistic way, but simultaneously we did not omit some critical reflections. The great idea of Space 4.0 should not be reduced only to a technical and simple business layer connecting the LEO zone to the Industry 4.0 economy. Space 4.0 contains also space based services. Space 4.0 is not only a simple ecosystem of small and cheap satellites. It is much more than this. We are proud participants of the Space 4.0, learning from mistakes, encouraging SMEs to be active, undertaking important administrative initiatives, to build real new, active societal space sector.